Pazopanib for renal cell carcinoma leads to elevated mean arterial pressures in a murine model. (18th August 2018) - Kempton, Amber; Justice, Cody; Guo, Aaron; Cefalu, Matthew; Makara, Michael; Janssen, Paul; Ho, Thai H; Smith, Sakima A
ABSTRACT: Background : In the setting of metastatic RCC (mRCC), pazopanib is approved as first line therapy. Unfortunately treatment may lead to cardiotoxicity such as hypertension, heart failure, and myocardial ischemia. Objective : Define the in vivo role of pazopanib in the development of cardiotoxicity. Methods : Wild type mice were dosed for 42 days via oral gavage, and separated into control and treatment (pazopanib) groups. Baseline ECG's, echocardiograms, and blood pressures were recorded. At the conclusion of the study functional parameters were again recorded, and animals were used for pathological, histological, and protein analysis. Results : After 2 weeks of dosing with pazopanib, the treatment group exhibited a statistically significant increase in mean arterial pressure compared to control mice (119 ± 11.7 mmHg versus 108 ± 8.2 mmHg, p  = 0.049). Treatment with pazopanib led to a significant reduction in the cardiac output of mice. Conclusion : Our findings in mice clearly demonstrate that treatment with pazopanib leads to a significant elevation in blood pressure after 2 weeks of dosing and this persists for the duration of dosing. The continued development of the cardio-oncology field will be paramount in providing optimal oncologic care while simultaneously improving cardiac outcomes through further investigation into the mechanisms of CV toxicity.